Does rafting promote contemporary gene flow? Global and regional patterns of population genetic diversity and structure on the false limpet Siphonaria lateralis in the Southern Ocean - Millán-Medina, Constanza; Lizama, Marcelo; Saucède, Thomas; Poulin, Elie; Segovia, Nicolás I.; González-Wevar, Claudio (Frontiers in Ecology and Evolution, 2024)
Rafting has been proposed as an effective mechanism for species without free-living pelagic larvae to achieve long-distance dispersal, theoretically preventing population differentiation over wide distributional ranges. Moreover, rafting has been advocated as a main dispersal mechanism for marine invertebrates with sub-Antarctic distributions, because of abundant buoyant kelps, driven by the Antarctic Circumpolar Current. Nonetheless, little attention has been given to the role of rafting to establish regular gene flow across the sub-Antarctic, and the geographic and temporal scales at which it occurs. Aiming to unravel these major questions about the extent of genetic connectivity across the Southern Ocean (SO), we studied the pulmonate limpet Siphonaria lateralis, a benthic species with encapsulated larvae, found on the rocky intertidal of sub-Antarctic islands and southern South America. Since S. lateralis is closely associated with D. antarctica, dispersal by rafting is plausible, as revealed by the absence of phylogeographic structure across the sub-Antarctic. We sampled 116 individuals from eight localities across the SO, and used 5,515 SNPs obtained through Genotyping-by-Sequencing, to determine contemporary genetic diversity, structure, and gene flow at two spatial scales; global, across the SO, and regional, within Kerguelen. Results identified substantial genetic structure, differentiating Patagonia, Falklands/Malvinas Islands, South Georgia and the Kerguelen archipelago, and low levels of contemporary gene flow. The most notable genetic differentiation was found between Patagonia/Falklands and South Georgia/Kerguelen. Structure was also significant between Patagonia and the Falkland/Malvinas Islands. Conversely, South Georgia and Kerguelen exhibited closer genetic affinity, and indications of recent but limited gene flow. Moreover, historical gene flow estimates between the four populations were low. At regional scale, noteworthy genetic structure persisted, and gene flow was insufficient to prevent genetic differentiation within Kerguelen. Consequently, rafting’s potential may be overestimated as a contemporary mechanism promoting gene flow across the SO, as these events may be sporadic, irregular, and unpredictable for marine invertebrates lacking a larval dispersal stage, since contemporary dispersal events don’t seem to facilitate high gene flow at both scales. Accordingly, other oceanographic factors or processes may hinder the establishment of species associated with macroalgae, and as consequence, contemporary genetic connectivity in the sub-Antarctic.